Hypoxia and Hypoxia-Inducible Factors in Lymphedema - Jiang, Xinguo; Tian, Wen; Kim, Dongeon; McQuiston, Alexander S.; Vinh, Ryan; Rockson, Stanley G.; Semenza, Gregg L.; Nicolls, Mark R. (Frontiers in Pharmacology, 2022)
Lymphedema is a chronic inflammatory disorder characterized by edema, fat deposition, and fibrotic tissue remodeling. Despite significant advances in lymphatic biology research, our knowledge of lymphedema pathology is incomplete. Currently, there is no approved pharmacological therapy for this debilitating disease. Hypoxia is a recognized feature of inflammation, obesity, and fibrosis. Understanding hypoxia-regulated pathways in lymphedema may provide new insights into the pathobiology of this chronic disorder and help developing new medicinal treatments.